Comparison of short- and long-term outcomes between isolated and concomitant tricuspid valve surgery - Amr A. Arafat; Haneen Alghosoon; Rawan Alghamdi; Monirah A. Albabtain; Huda Ismail; Adam I. Adam; Claudio Pragliola; Khaled A. Alotaibi (The Cardiothoracic Surgeon)
Abstract Background Accurate reflections of long-term outcomes of isolated tricuspid valve surgery are underreported in the literature. Most published cohort studies consisted of patients receiving tricuspid valve surgery concomitant with left-sided procedures. Patients who undergo isolated tricuspid valve surgery usually present late for surgery, with deteriorating risk factors leading to increased surgical risk. Thus, this study aimed to compare the short- and long-term outcomes of isolated tricuspid valve surgery with those of tricuspid surgery concomitant with left-sided valve procedures. This retrospective cohort study included 617 patients who underwent isolated and left-sided concomitant tricuspid valve surgery from 2009 to 2020. We grouped the patients into isolated (n = 63) vs. concomitant tricuspid surgery (n = 554). Results Isolated tricuspid surgery was associated with significantly greater rates of operative mortality (19% vs. 5.2%, P < 0.001), renal failure requiring dialysis (12.7% vs. 2.71%, P < 0.001), and need for ventilation > 24 h (22.22% vs. 12.27%, P = 0.028). ICU (3 days vs. 2 days, P = 0.005) and hospital stays (13 days vs. 11 days, P = 0.042) were significantly longer in isolated tricuspid surgery patients. Isolated tricuspid surgery independently predicted hospital mortality (OR: 4.00 (95% CI: 1.59–10.05), P = 0.003). The risk of follow-up mortality was higher in patients with isolated surgery (HR: 1.95 (95% CI: 0.98–3.86); P = 0.055). However, isolated tricuspid surgery was not associated with heart failure rehospitalization (HR: 1.11 (95% CI: 0.51–2.41); P = 0.798) or increased tricuspid valve reinterventions (HR: 1.42 (95% CI: 0.51– 3.92); P = 0.499). Conclusions Isolated tricuspid surgery independently predicted hospital mortality and was associated with nonsignificantly higher long-term mortality. This finding highlights the importance of timely referral and intervention for patients with isolated tricuspid valve disease to optimize short- and long-term outcomes.